The Migration Industry and the Commercialization of International Migration - Gammeltoft-Hansen, Thomas; Nyberg Sorensen, Ninna (Global Institutions, 2013)
Migration has become business, big business. Over the last few decades a host of new business opportunities have emerged that capitalize both on the migrants' desires to migrate and the struggle by governments to manage migration. From the rapid growth of specialized transportation and labour immigration companies, to multinational companies managing detention centres or establishing border security, to the organized criminal networks profiting from human smuggling and trafficking, we are currently witnessing a growing commercialization of international migration. This volume claims that today it is almost impossible to speak of migration without also speaking of the migration industry. Yet, acknowledging the role the migration industry plays prompts a number of questions that have so far received only limited attention among scholars and policy makers. The book offers new concepts and theory for the study of international migration by bringing together cross-disciplinary theoretical explorations and original case studies. It also provides a global coverage of the phenomena under study, covering migrant destinations in Europe, the United States and Asia, and migrant sending regions in Africa, Asia and Latin America.